Studi Kasus Putusan Pengadilan Negeri Jakarta Pusat Nomor 1140/PID.SUS/2020/PN JKT PST Tentang Perbuatan Melaksanakan Tindakan Aborsi Ilegal - Medhira Iswara; Agus Takariawan; Ajie Ramdan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Pregnancy can be good or bad depending on the condition of the mother. Some mothers who do not want their babies choose to have illegal abortions. This has led to the proliferation of illegal abortion clinics that perform abortions not in accordance with the law. Although the law provides for some justifiable cases of abortion, there is debate about the consequences of punishing abortionists. Judges' verdicts in abortion cases often do not fulfil the purpose of punishment to provide a deterrent and corrective effect. The purpose of this research is to analyse the Case Study of Central Jakarta District Court Decision Number 1140/pid.sus/2020/Pn Jkt Pst on the act of carrying out illegal abortion in accordance with Article 75 of Law Number 36 of 2009 concerning health in relation to the purpose of punishment. This research method is a normative juridical approach. The research specifications used are descriptive analysis. The result of this research is that the Panel of Judges in this case can be considered lacking in considering the mitigating or aggravating circumstances of the defendant when compared to other cases. Consideration of judges who are less mature can lead to unclear objectives of punishment in cases of abortion. The clarity of the human rights of a foetus is questionable in this abortion case. More research and careful consideration by judges is needed to ensure fair and balanced sentencing in abortion cases.